NUEVA LOCALIDAD EN CHILE PARA MENODORA LINOIDES PHIL. (OLEACEAE), ESPECIE CONSIDERADA EXTINTA EN EL SIGLO XX - Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés; León-Lobos, Pedro (Gayana Botánica, 2006)
An area in the Andes of the Valparaíso Region is indicated as a new locality for the species Menodora linoides Phil., an endemic and unique representative of the Oleaceae family in Chile. The plant described in 1863, was considered extinct in the 20th century, but has been collected twice in the present century.